Greater Mekong Sub-region Options for the Structure of the GMS Power Trade Market : A First Overview of Issues and Possible Options - World Bank (World Bank, Washington, DC, 2014)
The World Bank, working together with the Asian Development Bank (ADB), actively supports the development of a regional power market in the GMS: Cambodia, Lao PDR, Myanmar, Thailand, Vietnam and the Yunnan Province of the People's Republic of China. This report is part of a dynamic process aimed at developing power trade in the Greater Mekong Sub-region (GMS), the objective of which will be to provide reliable and economic electric service to consumers, consistent with sustainable use of natural resources. The report includes the following headings: introduction; issues related to the current situation; possible options and requirements for the intermediate term; recommendations for intermediate-term decisions; options for long-term trading in the GMS region; next steps; and conclusion.